Public policy targets in EU broadband markets: The role of technological neutrality. (June 2020) - Briglauer, Wolfgang; Stocker, Volker; Whalley, Jason
Abstract: The European Commission has recently sought to substantially revise how it regulates the telecommunication industry, with a key goal being to incentivise investment in high-speed broadband networks. Ambitious goals to incentivise investment in high-speed broadband networks have been set across the European Union, initially in the 'Digital Agenda for Europe' and more recently in its 'Gigabit strategy'. These goals reflect the view of many that there are widespread and significant socio-economic benefits associated with broadband. Our analysis explores the consequence of target setting at a European level, in terms of encouraging investment and picking which technology should be adopted within the context of technological neutrality. We demonstrate that while public policy targets might implicitly favour specific technologies, especially when gigabit targets are defined, the technological choices that occur within individual Member States are shaped by the complex and dynamic interaction between a series of path dependencies that may vary significantly across as well as within Member States. Adopting an ecosystem perspective, we propose a conceptual framework that identifies the key factors associated with technological neutrality and informs a rational decision-making process. Highlights: We examine the concept of technological neutrality within the context of the policy targets that the EU has adopted. Our analysis identifies key factors whose interdependencies guide a rational decision-making process. The interaction between a series of path dependencies limits the ability of the EU to mandate a harmonized approach. The key role to be played by technological neutrality is achieving the objectives but not prescribing the means to do so.